A Framework for Learning about Emotion and Emotionality in Organizational Systems as a Core Aspect of Leadership Development.. - James, Kim; Arroba, Tanya (SAGE Publications, 2005)
This article outlines a developmental framework for introducing systems psychodynamic concepts in the context of leadership development. The model focuses on two key aspects of the leadership role needed in today’s organizations. These are the ability to Read what is less obvious and below the surface in organizational systems, and the ability to manage what is Carried by those in leadership roles. These abilities inform choice of behaviours and intervention by leaders in their organization systems. We argue for the need for appreciation of the systems psychodynamics within organizations and identify the difficulties in including these aspects in leadership development programmes. This article provides a case study of a leadership development programme where we use the ‘Reading and Carrying’ model as a bridge to understanding the emotion/ality that impinges on the leadership role. We discuss the difficulties that learning about emotion in and of the system can bring, by looking at the emotion raised in the learning experience.